Association Between Preoperative Malnutrition and Postoperative Delirium After Hip Fracture Surgery in Older Adults. Issue 6 (6th March 2017) - Mazzola, Paolo; Ward, Libby; Zazzetta, Sara; Broggini, Valentina; Anzuini, Alessandra; Valcarcel, Breanna; Brathwaite, Justin S.; Pasinetti, Giulio M.; Bellelli, Giuseppe; Annoni, Giorgio
Abstract : Objectives: To determine whether poor nutritional status can predict postoperative delirium in elderly adults undergoing hip fracture surgery. Design: Prospective observational cohort study. Setting: Italian orthogeriatric unit. Participants: Individuals aged 70 and older (mean age 84.0 ± 6.6, 74.5% female) consecutively admitted for surgical repair of a proximal femur fracture between September 2012 and April 2016 (N = 415). Measurements: Participants underwent a comprehensive geriatric assessment including nutritional status, which was evaluated using the Mini Nutritional Assessment Short Form (MNA‐SF). The MNA‐SF‐based three‐class stratification was tested using multivariable logistic regression to assess its role in predicting postoperative delirium (outcome). Results: Seventy‐eight malnourished individuals (MNA‐SF score 0–7), 185 at risk of malnutrition (MNA‐SF score 8–11), and 152 who were well nourished (MNA‐SF score 12–14) were compared. On average, individuals with poor nutritional status were more disabled and more cognitively impaired than those who were well nourished and those at risk of malnutrition. Moreover, those who were malnourished were more likely to have postoperative delirium. Multivariate regression analysis adjusted for age, sex, comorbidity, functional impairment, preoperative cognitive status, and American Society of Anesthesiologists score showed that those who were at risk of malnutrition (odds ratio (OR) = 2.42, 95% confidence interval (CI) = 1.29–4.53) and those who were overtly malnourished (OR = 2.98, 95% CI = 1.43–6.19) were more likely to develop postoperative delirium. Conclusion: This is the first study in a Western population showing that risk of malnutrition and overt malnutrition, as assessed using the MNA‐SF, are independent predictors of postoperative delirium. Accordingly, nutritional status should be assessed in individuals with hip fracture before surgery to determine risk of developing delirium.